Stability Constant of Transition Metal Complexes Aryl Schiff Bases - Naikwade, S.D.; Mane, P.S.; Chondhekar, T.K. (Asian Journal of Chemistry, 2010)
Proton ligand stability constants of p-bromo-OHA -N -( 4' -methyl- phenyl) imine (R1), 5-bromo-OHA-N-(5-nitrophenyl) imine (R2) and 5-bromo-OHA-N-(2-chloro-5-nitrophenyl) imine (R3) and metal-ligand stability constants of their complexes with transition metals Cu(II), Ni(II), Co(ll), Mn(II) and Cd(II) have been determined at 25°, 35° and 45°C (± 0.1 oC) and μ = 0.1 M (NaCIO4) in 50 : 50 ethanol-water medium. The thermodynamic parameters for the formation of 1 : 1 and 1 : 2 complexes have been calculated. The effect of substituent and the dependence of stability constants on the atomic size has been discussed.